The Two-Good-Neighbor Connectivity and Diagnosability of the Augmented Three-Ary n-Cubes. (12th December 2018) - Wang, Shiying; Zhao, Nan
Abstract: Connectivity and diagnosability of a multiprocessor system are discussed by many researchers. As a favorable topology structue, the augmented three-ary n -cubes A Q n, 3 has many good properties. In this paper, we prove that the two-good-neighbor connectivity of A Q n, 3 is 12 n − 24 for n ≥ 4, and the two-good-neighbor diagnosability of A Q n, 3 is 12 n − 22 for n ≥ 4 under the PMC model and MM * model.